Incontinence in persons with tuberous sclerosis complex. Issue 6 (15th June 2020) - Clasen, Oriana; Hussong, Justine; Wagner, Catharina; Flotats‐Bastardas, Marina; Meyer, Sascha; Zemlin, Michael; von Gontard, Alexander
Abstract: Aims: Tuberous sclerosis complex (TSC) is a multisystem genetic disorder caused by a mutation in the TSC1 or TSC2 gene with a broad spectrum of physical and psychological manifestations. The aim of the study was to examine incontinence, psychological problems, and adaptive behavior skills in patients with TSC. Methods: Through a worldwide TSC support group, 26 children (4‐17 years) and 15 adults (18‐50 years) with TSC were recruited (38.1% male, mean age 16.4 years). Parents or care‐givers completed the Developmental Behavior Checklist (DBC), the Parental Questionnaire: Enuresis/urinary Incontinence, and the Vineland Adaptive Behavior Scales (3rd edition). Results: A total of 60.0% of the participants had nocturnal enuresis (NE), 51.3% daytime urinary incontinence (DUI) and 52.4% fecal incontinence (FI). 65.4% of children and 50.0% of adults had a clinically relevant DBC score. Psychological symptoms were associated with at least one subtype of incontinence. The mean adaptive behavior composite (ABC) score of the patients was 57.2 (SD = 26.1), with 38.1% in the average or below‐average range (IQ >70), 26.2% with a mild, 11.9% with a moderate and 23.8% with a severe/profound intellectual disability. The incontinence rate was significantly higher in the groups with a lower ABC score. Conclusion: A substantial proportion of patients with TSC are affected by incontinence and psychological symptoms. Incontinence was higher in persons with lower adaptive skills and those with at least one type of incontinence showed a significantly higher DBC score. As incontinence and psychological problems affect daily functioning and well‐being, assessment, and treatment are recommended.